Survival of a Grossly Decayed Premolar; Novel Technique of Surgical Extrusion for Faster Clinical Crown Lengthening: a Case Report - Dr Kundabala Mala (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Clinical crown lengthening can be brought about by surgical gingivectomy, orthodontic extrusion of tooth or surgical extrusion of tooth. This technique allows us to extrude the root, in a single visit, short period of time without violating the biological width. Following is a case requiring clinical crown lengthening where novel technique of surgical extrusion is demonstrated along with the treatment outcome along with one and eight months follow up. A 38 year old female patient reported to dental clinic with a chief complaint of decayed upper left tooth accompanied with no pain. Upon examination, grossly decayed premolar (24) was present. The line of treatment followed in the conservative option was to save the natural tooth by extruding the tooth following which root canal treatment with a suitable post endodontic restoration was performed. The absence of any periodontal or periapical pathology, well formed root with absence of symptoms, adequate crown and root ratio, absence of any systemic condition and a fairly young age promoting healing recommended the use of surgical method to gain length of crown followed by RCT and a suitable post endodontic restoration which further showed no clinical or radiographic symptoms reappearing in 8 months post operatively. Thus, with appropriate diagnosis, and absolute indications, surgical extrusion proves to be atraumatic, faster, conservative, cost effective and functionally stable method of gaining crown height, in grossly destructed tooth